Gold and Ceria as Catalysts for VOC Abatement: A Review - Gaálová, Jana; Topka, Pavel (Catalysts, 2021)
Due to its excellent oxygen storage capacity, ceria is a well-known oxidation catalyst. However, its performance in the oxidation of volatile organic compounds can be improved by the introduction of gold. Depending on the type of VOC to be oxidized, the surface of gold nanoparticles and the gold/ceria interface may contribute to enhanced activity and/or selectivity. Choosing a proper preparation method is crucial to obtain optimal gold particle size. Deposition–precipitation was found to be more suitable than coprecipitation or impregnation. For industrial applications, monolithic catalysts are needed to minimize the pressure drop in the reactor and reduce mass and heat transfer limitations. In addition to the approach used with powder catalysts, the method employed to introduce gold in/on the washcoat has to be considered.